Simulation of Landscape Pattern of Old Growth Forests of Korean Pine By Block Kriging - 王政权 张颜东 王庆成 HarbinLi (Journal of forestry research, 1997)
The study area was located in Liangshui Natural Reserve. Xaoxing’an Mountains. Northeastern China Korean pine forests are the typical forest ecosystem and landscapes in this region. It is a high degrees of spatial and temporal heterogeneity at different scales, which effected on landscape pattern and processes. In this paper we used the data of 144 plots and semivariogram to analyze spatial heterogeneity of old growth forests of Korean pine in landscape level. Model for forest variations by isotropic semivariogram is linear with sill. The spatial heterogeneity is dependent on scales and directions in Korean pine forests. Patterns of forest types in space were resulted from complex interactions between physical and biological forces. We used 20 metres for interpolation interval to estimate the values of unsampled area. Comparing the results with field data, block kriging and mapping are an effective techniques to simulate landscape pattern.